Anatomical reduction and precise internal fixation of intra-articular fractures of the distal radius with virtual X-ray and 3D printing - Jing Xu; Guodong Zhang; Zaopeng He; Shizhen Zhong; Yongshao Chen; Chunrong Wei; Yudong Zheng; Haibin Lin; Wei Li; Wenhua Huang (Physical and Engineering Sciences in Medicine, 2020)
To evaluate and precisely internal fix intra-articular distal radial fracture (IDRF) using the virtual X-ray and three-dimensional (3D) printing technologies. Twenty-one patients with IDRF were recruited, and the data from digital design group (DDG) and real surgery group (RSG) were collected and analyzed. In DDG, the data from thin-slice computed tomography scan, virtual X-ray measurement parameters, including volar tilt, palmar tilt, radius length (D1), ulnar variation (D2), locking plate position parameter (D3) and distance between key nail and joint surface (D4) were collected. The bone was virtually fixed with the locking plate, and the final model of radius with the screw was obtained by 3D printing. In RSG, the locking plate was precisely pre-bended and used in surgery. During the surgery, the key K-wire was accurately placed and the locking plate was adjusted with the aid of the U-shaped navigation arm. The C-arm was used to observe the positions of key K-wires and the locking plate, and the same above-mentioned parameters were measured intra- and post-operatively. The data from RSG and DDG were compared statistically by t test. This approach proved to be successful in all 21 patients, and none of the screws pierced through the wrist joint surface. All the measured parameters, including the volar tilt, palmar tilt, D1–4, in RSG were not significantly different from preoperative DDG data. Virtual X-ray measurement of anatomical reduction parameters and 3D printing can help the anatomical reduction and precise internal fixation by providing quantitative references, preoperatively, intraoperatively and postoperatively.